TANGGUNGJAWAB PEMEGANG SAHAM DALAM PERPANJANGAN HAK GUNA USAHA (PUTUSAN MA NOMOR 1480K/PDT/2013) - YANTI AGUSTINA (PREMISE LAW JURNAL, 2017)
The case in the Ruling of the Supreme Court started with the extension of the Leasehold of anentity named PT.Pertekstilan TD.Pardede. According to the Law No.5/1960 on the Land Actwhich states that the Leasehold of an entity can be extended. The party who is liable for theextension of the Leasehold is the director, pursuant to the Law No. 40/2007 on Limited LiabilityCompany. However, when arranging the extension of the Leasehold, the director found obstaclesbecause the Leasehold Certificate was being saved in the safe deposit box blocked by theshareholder of PT.Pertekstilan TD.Pardede causing loss to the company. The research is doneby employing the normative juridical approach with descriptive analysis. The results show thatthe handing of the Leasehold to an entity must be completed with the decree of the ministery ofjudge concerning entity Legalization and announced in the state news, a reference letter from astate bank which shows the applicant’s bonafides, preliminary study in affording the land andexpert availability. The shareholder’s liability for the extension of the leasehold is enforceableto, in this case, open the safe deposit box so that the Leasehold Certificate can be taken andsubmitted to BPN (the Land Office) for the Leasehold Extension. The consequence for notextending the Leasehold is that it will be eliminated, and the land will be returned to bepossessed by the state.Keywords: Shareholder, Extension, Leasehold